2018
DOI: 10.21009/jsq.014.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Education on Science, Peace, and Development in Thought of Said Nursi

Abstract: Bediüzzaman Said Nursi desired to fit in the divine and modern knowledge with the resolution to authenticate the facts for assurance. To overcome many obstacles and continued in the teaching of Islam requires education to inspire learning approach across all societies. Development is more effective when it is combined with Character and religious education. Therefore he thrived to release the Islamic world from the dungeons of ignorance and poverty; with vision and progressive action, believed that a greater d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…A teacher plays a vital part in building student character (Abdullah et al, 2019). Nursi recommends expertise in a multi-disciplinary study program, where each student should focus on lessons constructed and aligned with his talents and learn other subjects that complement them (Said, 2018). The ideal teacher is intelligent, perfectly minded, and has good morals and physical strength.…”
Section: The Methods Of Said Nursi Educationmentioning
confidence: 99%
“…A teacher plays a vital part in building student character (Abdullah et al, 2019). Nursi recommends expertise in a multi-disciplinary study program, where each student should focus on lessons constructed and aligned with his talents and learn other subjects that complement them (Said, 2018). The ideal teacher is intelligent, perfectly minded, and has good morals and physical strength.…”
Section: The Methods Of Said Nursi Educationmentioning
confidence: 99%
“…Topik yang paling banyak menyita perhatian Said Nursi adalah persoalan hubungan sains dan Islam (Said, 2018). Sejak pembaruan 'tanzimat' Ottoman hingga berdiri Turki modern (Hanioglu, 2005), filsafat materialism yang menyertai sains digemari kalangan intelektual Turki (Poyraz, 2010).…”
Section: Pembahasan Kelahiran Gerakan Nurcuunclassified
“…Nurcu tidak menyalahkan Ottoman maupun budaya umat Islam. Kelompok Nurcu menegaskan bahwa kemunduran umat Islam disebabkan oleh kegagalan dalam membangun sistem pendidikan yang dapat mengintergrasikan antara modernitas dan agama (Said, 2018). Teknologi bisa saja didatangkan dari luar negeri, ujar mereka, tetapi sumber daya manusia yang menentukan penggunaan teknologi.…”
Section: Perkembangan Nurcu Menjadi Gerakan Kulturalunclassified
“…Moreover, Zarrouk et al [49] and Hassan and Bashir [50] defined that there is a strong relationship between the profitability and effectiveness of banks. In addition to the mentioned studies, Said [51], Devi and Rusydiana [52], and Makttoof and Khalid [53] identified that banks should invest in technological issues in order to increase their efficiency. According to some authors, effective customer relations play an important role in this context [54,55].…”
Section: Literature Reviewmentioning
confidence: 99%